Isotopic signature and the trophic interactions of Aegla castro Schmitt, 1942 (Crustacea: Anomura: Aeglidae) - Denadai, Ana Clara [UNESP]; Costa, Vladimir Eliodoro [UNESP]; Wolf, Milena Regina [UNESP]; Lemos Goncalves, Geslaine Rafaela; Castilho, Antonio Leao [UNESP] (Soc Brasileira Carcinologia, 2022)
Aeglids are endemic crustaceans from the Neotropical region of South America, with great importance in the freshwater food chain. We investigated the trophic relationships in different streams containingAegla castro Schmitt,1942 through the use of stable isotopes, testing the hypothesis that these animals occupy a lower position and that the environments are different and will modulate the isotopic ratios of carbon and nitrogen. Aegla castro showed a low trophic level in all locations, being an important link between producers and other trophic levels. They present differences in their isotopic signature for the sampling areas, indicating that environment can be a factor that modulates the trophic webs. We did not find intraspecific differences in isotopic signatures, probably due to the similar food items consumed by both juveniles and adults foraging in the same locations. Studies like this are becoming increasingly important due to the rapid degradation of freshwater environments and the lack of trophic knowledge about these endemic animals. It is increasingly important to understand how environmental changes (such as through anthropogenic action) is interfering in freshwater trophic relationships, and how this can affect the permanence of aeglids.
Keywords: Carbon; environmental characteristics; food web; nitrogen; ontogenetic phases